Effects of Micro Role-Play on Child Sexual Abuse Prevention Knowledge among Primary School Children in Medan, Indo-nesia - Srimis Leini Saragih; Zuidah Zuidah; Rahma Dani (Green Health International Journal of Health Sciences Nursing and Nutrition, 2026)
Child sexual abuse remains a major threat to children’s safety, while many primary-school children have limited knowledge of private body parts, unsafe touch, refusal skills, and help-seeking. This study examined whether a micro role-play intervention improved knowledge of child sexual abuse prevention among third-grade students. A one-group pretest-posttest pre-experimental design was conducted in 2025 at SD Negeri No. 060827 Medan, Indonesia. Thirty students aged 8–9 years were selected through purposive sampling. The intervention used small paper puppets and scripted scenarios to model body-safety rules, responses to grooming attempts, refusal, escape, and disclosure to trusted adults. Knowledge was measured before and immediately after the session using a 15-item questionnaire. Because score distributions were non-normal, paired scores were analyzed using the Wilcoxon signed-rank test. Before the intervention, 17 students (56.7%) had low knowledge, nine (30.0%) had moderate knowledge, and four (13.3%) had good knowledge. After the intervention, 26 students (86.7%) had good knowledge and four (13.3%) had moderate knowledge. The median score increased from 53.3 (interquartile range 53.3–73.3) to 93.3 (86.6–93.3). All participants improved, and the change was statistically significant (W = 0, p < 0.001; r = 0.88). Micro role-play produced a substantial immediate improvement in prevention knowledge and may be a feasible, developmentally appropriate approach for school-based safety education. Controlled studies with longer follow-up are required.